Performance-based Aid, Enhanced Advising, and the Income Gap in College Graduation: Evidence From a Randomized Controlled Trial - Erwin, C; Binder, M; Miller, C; Krauss, K (SAGE Publications, 2021)
Income gaps in college enrollment, persistence, and graduation raise concerns for those interested in equal opportunity in higher education. We present findings from a randomly assigned scholarship for low-income students at a medium-sized public 4-year university. The program focused solely on the first four semesters of enrollment and tied aid disbursements to modest academic benchmarks and enhanced academic advising. Meaningful decreases in time to degree appear to be driven by students with the lowest academic preparation and family income. Treated students took out approximately 20% less in student loans during the duration of the program. Participants also indicated high satisfaction with the program’s model of enhanced academic advising.
Keywords: Achievement gap; Counseling; Economics of education; Educational policy; Higher education; Postsecondary education; Econometric analysis; Experimental design; Experimental research